Flipped Classrooms in the Digital Age: A WhatsApp-Based Approach to Improving Reading Comprehension Across Genders - Katemba, Caroline Victorine; Setyaningtyas, Rida A.; Tobing, Jonathan H. (LPPM Universitas Advent Indonesia, 2025)
Reading comprehension is one of the most important in learning English.This study aimed to find out improving students’ reading comprehension using Flipped Classroom through WhatsApp. The sample in this research is 8th grade students from two classes at SMPN 10 Cimahi in grade eight. This research using quantitative approach and using experimental method. The student’s (female and male) reading comprehension ability show improvement. It show from the mean score for n-gain in male 0.4280 and from female is 0.5613 it means the initial ability after using Flipped Classroom through Whatsapp male and female in students’ reading comprehension is increase. In, addition, There is difference in students’ reading comprehension improvement between female and male students after being taught using flipped classroom through WhatsApp, it shows from the result of independent sample T-test is 0,001 > 0,005. The result from the questionnaire is 93.33% responded positively. In summary, it can be conclude that the Flipped Classroom through WhatsApp can help the students in reading comprehension.